The Strategy of Teaching Arabic Composition in The Arabic Language Development Center at Pondok Pesantren Darul Lughah Wal Karomah Kraksaan Probolinggo Indonesia | Istirotijiyah Ta'lim al-Insya' fiy Markaz Tabahhur al-Lughah al-'Arabiyah bi Ma'had Darul L: إستراتيجية تعليم الإنشاء في مركز تبحر اللغة العربية بمعهد دار اللغة والكرامة كركسأن بروبولنجو إندونيسيا - Edi Kurniawan Farid; Aisyatur Rodhiyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This research aims to know theteaching Arabic Composition and it's strategy in the Arabic language development center at Pondok Pesantren Darul Lughah Wal Karomah Kraksaan Probolinggo Indonesia. The qualitative approach used by researcher with the type of case study. For collecting the data, the researcher used observation, interview, and documentation. To analyze the data, this research based on interactiv data analysis by miles and huberman, and for measuring the validity of data, this research used data triangulation. The results of this research arethe teaching Arabic Compositionin the Arabic language development centerat Pondok Pesantren Darul Lughah Wal Karomah is held once for every two weeks. And for each level used a different methode. Every night, after madrasah diniyah time at at eight to nine thirty, the teaching of qowa'id lesson and tarkib al-jumlah as-shohihah lesson are held.Forteaching Arabic Compositionin the Arabic language development center, the teacher uses teaching strategies, including composing sentences from new mufrodat, composing story in groups, and composing essay to fill in the wall magazines.